Ekonomi Kreatif Dengan Program Warung Keluarga Melalui Budidaya Ikan Dalam Ember - Margiyono Suyitno; Sukamdi Sukamdi; Eskawida Eskawida (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Budikdamber or known as Fish Cultivation in a Bucket is a form of creative economy business that can be done in a family in order to fulfill some basic needs. This research is a Research and Development, which is to continue and modify various findings and problems in the implementation of Warung Keluarga through Budikdamber. The discussion and report models use a qualitative approach. This research was conducted in several places in Boyolali in 2020, 2021, and early 2022. The results show that the Warung Keluarga program through Budikdamber can be done easily, does not require a large space, large capital, and is side-by-side. However, it will result in a significant economic increase in meeting the basic needs of the family, and can be used as a business opportunity if taken seriously. The Budikdamber program can be developed through the media of drums, Pengaron, Plastic Sheeting, and Permanent Pools. Catfish harvest success rate 75% - 95%. The success for the types of catfish and gourami can reach 90% - 98%.